Pengaruh Promosi Gratis Ongkos Kirim, Iklan, dan Celebrity Endorsement Terhadap Keputusan Pembelian Ditinjau dari Platform Shopee dan Tiktok - Hapnida Siregar; Yuniman Zebua; Syukron Arjuna (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to determine the effect of free shipping promotions, advertising and celebrity endorsements on purchasing decisions reviewed from the Shopee and TikTok platforms. This type of research is associative research. Data collection in this study was carried out through a survey approach with a quantitative descriptive research type by distributing questionnaires to 86 respondents. Data collection techniques were carried out using interviews, questionnaires and documentation studies. The data analysis tool used in this study used SPSS. The data analysis technique in this study is descriptive analysis. The results of the study indicate that free promotions, advertising and celebrity endorsements influence purchasing decisions both partially and simultaneously. It can be seen from the results of the determination coefficient of 0.623. This value means that purchasing decisions can be explained by free shipping promotions, advertising and celebrity endorsements by 62.3%. While the remaining 37.7% is influenced by other variables not examined in this study.